A Novel Three-Vector-Based Model Predictive Direct Power Control for Three-Phase PWM Rectifier - Liuchen Tai (MDPI AG, 2021)
A novel strategy of three-vector-based model predictive direct power control (MPDPC) is proposed for three-phase Pulse-width Modulation (PWM) rectifier. Under ideal grid conditions, three-vector MPDPC is studied, and a good control effect has been achieved. However, under the unbalanced power grid condition, the traditional control strategy has some problems, such as a high harmonic content of current and large instantaneous power pulsation. A new three-vector model predictive control is proposed based on the new instantaneous power theory, and the objective function is established by instantaneous power error. The duty cycle of the selected vector is calculated by solving the optimal objective function. Under an unbalanced power grid, this paper takes a three-phase PWM rectifier as a research object, and carries out simulation and experimental tests on the traditional and new control strategies. The experimental results show that the new control strategy has lower current harmonics, and eliminates the twice grid-frequency oscillation of the grid in instantaneous power.